Pengaruh Lokasi terhadap Keputusan Berkunjung Wisata Rania Hot Spring Kecamatan Ulu Barumun Kabupaten Padang Lawas - Mahrani Azis; Sari Fitri; Muhlisah Lubis (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this study is to determine how much location influences visitors' decisions regarding whether or not to visit the Aek Milas Rania Hot Spring Baths tourist attraction. A quantitative method, accidental sampling testing is used to describe information in the research strategy. 92 individuals comprised the quantitative sample for this study, which was conducted with SPSS version 21. By utilizing the t test to dissect the information, the t count was 17.585 and the t table with an importance level of 5% was 1.665, which shows that the t count was more prominent than the t table. This demonstrates that location influences a person's decision to visit the Aek Milas Rania Hot Spring tourist attraction in the Ulu Barumun District of the Padang Lawas Regency.